PENERJEMAHAN KALA BAHASA ARAB DALAM BAHASA INDONESIA - Supardi Supardi (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
This article examines the translation of Arabic tenses expression into Indonesian. This library research employs a descriptive analysis method based on Catford’s theoretical translation framework. This study finds that, firstly, from the extension of translation perspective, the tense expression in Arabic can be translated fully into Indonesian, in which all of the Arabic tense expression has the Indonesian equivalence. Linguistically speaking, in certain cases the translation of Arabic verbs both mādī (perfect) and mudāri’ (imperfect) has to be added with an Indonesian temporal adverb. The auxiliary verb kāna, which usually combined with mudāri’ verb in Arabic past tense is translated into Indonesian adverb of time: “dulu”, “dahulu”, or “tadi”. Secondly, the expression of Arabic future tense, which constitutes mudāri’ verb, prefix “sa_” or particle “saufa,” is also translated into “akan”. The mādī (perfect) verb, which is used in the context of wishing, is translated into Indonesian equivalence verb - “semoga”. Thirdly, In translating Arabic into Indonesian, context (siyāq) comes into play, not all Arabic verbs denotes definite tense in a sentence